Genome-Wide Comparative Analysis of HIF Binding Sites in Cyprinus Carpio for In Silico Identification of Functional Hypoxia Response Elements - Rashid, Iliyas; Pathak, Ajey Kumar; Kumar, Ravindra; Srivastava, Prachi; Singh, Mahender; Murali, S; Kushwaha, Basdeo (Frontiers in Genetics, 2019)
The tolerance potential against hypoxia relates to induced gene expression. The HIF needs to bind to a transcriptionally active site HRE (5'-RCGTG-3') within promoter/enhancer region of a gene for inducing the expression and preventing/minimizing the hypoxia effects. HRE is functionally active when it contains a HAS (5'-CA(G|C)(A|G)(T|G|C)-3') typically adjacent to its downstream within 7-15 nt space. Here, an attempt was made for mining HRE and identifying functionally HBS in genome-wide analysis of Cyprinus carpio, which is highly hypoxia tolerant species. Gene information and the 5,000 nt long upstream (-4900 to +100) sequences of 31,466 protein-coding genes were downloaded from ‘Gene’ and ‘RefSeq’ databases. Analysis was performed after filtration of impracticable genes. A total of 116,148 HRE consensus sequences were mined from 29,545 genes in different promoter regions. Observation frequency of HRE with HAS consensus motifs were found in promoter region of 9,589 genes. An interactive user interface ‘HREExplorer’ was developed for presenting results on world-wide-web and visualizing HBS in protein-coding genes in chromosomal view. Reported hypoxia-responsive genes in zebrafish were reanalyzed and results used for comparative analysis. It is a novel work that may provide a great insight for analyzing genes in the hypoxia susceptible fishes of cyprinidae family.